2016
DOI: 10.1039/c6ra18032a
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric investigations on poly(vinylidene fluoride)/NiFe2O4flexible films fabricated through a solution casting method

Abstract: Here we report magnetoelectric cross-coupling in poly(vinylidene fluoride)/NiFe2O4 flexible films and their polarization values, which are highly dependent on the percentage of ferroelectric β phase present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…The J-E curve resembles a buttery loop which is an obvious characteristic loop of a ferroelectric material. 44 The current density for neat PVDF at À10 V cm À1 is $0.5 nA cm À2 , and with the addition of MWCNTs and APTES-functionalized MWCNTs the current densities reduced to $0.3 and $0.2 nA cm À2 . This result indicated that the addition of MWCNTs and MWCNT-APTES NPs into the PVDF matrix reduced the leakage current.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…The J-E curve resembles a buttery loop which is an obvious characteristic loop of a ferroelectric material. 44 The current density for neat PVDF at À10 V cm À1 is $0.5 nA cm À2 , and with the addition of MWCNTs and APTES-functionalized MWCNTs the current densities reduced to $0.3 and $0.2 nA cm À2 . This result indicated that the addition of MWCNTs and MWCNT-APTES NPs into the PVDF matrix reduced the leakage current.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…A number of preparation methods have been reported for PVDF-based nanocomposites films using magnetic nanoparticles, such as PVDF-BiFeO 3 [26], PVDF-CoFe2O4 [27,28], PVDF-NaNbO 3 -Ni [12], PVDF-HFP/clay/NF [29], and PVDF-NiFe 2 O 4 [30,31], using either a solution casting, hot press, or electrospinning to improve the magneto-electric coupling. In those studies, enhancements in magneto-electric coupling and dielectric constant with the increase in filler nanoparticles were reported.…”
Section: Introductionmentioning
confidence: 99%
“…PVDF-TiO 2 nanocomposites have been developed [10] for application in separation membranes, which showed enhanced fouling resistance. Ferrimagnetic NiFe 2 O 4 nanoparticles were added to PVDF [11] in order to obtain composites, combining the ferroelectric and piezoelectric properties of PVDF and the magnetic properties of NiFe 2 O 4 . The addition of NiFe 2 O 4 nanoparticles resulted in enhanced formation of ferroelectric β phase of PVDF [12].…”
Section: Introductionmentioning
confidence: 99%